2010
DOI: 10.1086/655841
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Educational Intervention to Decrease Incidence of Central Line–Associated Bloodstream Infection (CLABSI) in Intensive Care Units with Low Baseline Incidence of CLABSI

Abstract: After an educational intervention in 3 intensive care units, 34 central line-associated bloodstream infections occurred in 11,582 central venous catheter [CVC]-days, compared with 45 episodes in 10,661 CVC-days before intervention (4.22 vs 2.94 episodes per 1,000 CVC-days [30.9% reduction]; P = .03, Wilcoxon rank sum test; P = .11, Poisson regression analysis).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 12 publications
0
35
1
2
Order By: Relevance
“…Multiple studies have shown that most, if not all, CLABSIs are preventable, and extensive guidelines have been developed in order to guide best practice for CVC placement (14). Successful strategies to reduce CLABSIs include the implementation of educational programs directed to the entire multidisciplinary ICU team (15)(16)(17)(18). These programs typically stress adherence to best practice behaviors known to prevent CLABSIs, including the use of full barrier precautions (19), skin prep at the insertion site (20), appropriate hand hygiene (21,22), and specifying the anatomic site of CVC placement (subclavian preferred to internal jugular preferred to femoral) (23)(24).…”
mentioning
confidence: 99%
“…Multiple studies have shown that most, if not all, CLABSIs are preventable, and extensive guidelines have been developed in order to guide best practice for CVC placement (14). Successful strategies to reduce CLABSIs include the implementation of educational programs directed to the entire multidisciplinary ICU team (15)(16)(17)(18). These programs typically stress adherence to best practice behaviors known to prevent CLABSIs, including the use of full barrier precautions (19), skin prep at the insertion site (20), appropriate hand hygiene (21,22), and specifying the anatomic site of CVC placement (subclavian preferred to internal jugular preferred to femoral) (23)(24).…”
mentioning
confidence: 99%
“…Some studies showed that education could be effective in reducing infection rates. Pérez-Parra et al, and Warren et al, demonstrated reduction of CRBSI rates from 4.22 to 2.94 and 4.90 to 2.1 episodes/1,000 catheter days, respectively, by using simple lectures and/or posters [30,31]. Other authors, who performed a pre-post interventional study by using an educational module, showed reduction in CRBSI rates by 66 % [27,32].…”
Section: Continuous Education and Training Of Healthcare Workersmentioning
confidence: 96%
“…The educational methods chosen should take into consideration the preferred methods of learning, principles of adult education, resources available, cultural norms, and languages spoken by health care personnel. 15,47,48 Engagement of the patient and family in CVC care bundles is imperative. Central venous catheter line rounds facilitated by nursing champions can be an important tool in CLABSI prevention.…”
Section: Strategies To Increase Compliance With Bundle Elementsmentioning
confidence: 99%